STRATEGI KOMUNIKASI BISNIS DI ERA DIGITAL (STUDI KASUS PT. PATRIA ANUGRAH SENTOSA MOTOR HONDA SUKARAME, BANDAR LAMPUNG) - Irawan, Dedi (STMIK Pringsewu, 2024)
This research aims to find out how to increase interest in buying PT products. Patria Anugrah Sentosa Sukarame, Bandar Lampung through business communication strategy planning in the digital era. The research method used is descriptive qualitative. The aim of the descriptive approach is to provide a comprehensive and in-depth description of the phenomenon being studied, which is then analyzed and interpreted (understood). The research results show that the marketing strategy which involves attractive promotions, maintenance services through a network of service centers, as well as a business communication approach that pays attention to aspects of quality, service, responsiveness and affordable prices, reflects the company's adaptation to market development theory and marketing business communication. In addition, promotional strategies that are integrated with the digital era, including the use of marketplaces and social media, show a positive response to demands in an era like today.